Measuring Social Exclusion: a Study from Turkey - Bayram, Nuran; Aytac, Serpil; Aytac, Mustafa; Sam, Neslihan; Bilgel, Nazan (Richtmann Publishing, 2011)
In this study we aimed to assess the feelings of social exclusion in a Turkish community. We used the Social Exclusion Scaledeveloped by Jehoel-Gijsbers & Vrooman. A total of 2493 volunteer participants were included in the study. We found that the feelingof social exclusion diminishes as people become older, and the length of residency in the city increases. Married people feel themselves lesssocially excluded than those who are divorced or widowed. Illiterate people feel themselves 4.4 times more socially excluded than those withuniversity degrees. People with a low economic level feel themselves 10.6 times more socially excluded than those at with a high economiclevel. People who do not own a home feel themselves 1.6 times more socially excluded than those with home ownership. In conclusion,25.0% of our study participants felt themselves socially excluded. We hope our research will provide an opening for further studies inTurkey.